Spectrum of Lesions of Gall Bladder: Experience of Five Years at Tertiary Care Hospital - Patil, Milind; Londhe, Mangesh Machindra; Margam, Sangeeta; Iqbal, Javed (Annals of Pathology and Laboratory Medicine, 2018)
Background : The histopathological spectrum of gallbladder lesions is extremely variable and its frequency in cholecystectomies is not clear. This spectrum varies from non- neoplastic lesions like cholecystitis, gall stones, cholesterolosis, hyperplasia to neoplastic disorders. As there is limited literature available especially from this part of India, the aim of this study is to find incidences of various lesions of gall bladder in a tertiary care hospital. Methods: Five years retrospective and prospective analysis of 1096 cholecystectomies was carried out. Relevant clinical details of patient were noted down. Cholecystectomy specimens were studied for gross and microscopic examination after fixation of specimen with 10% formalin and microscopically examining H& E slides. Results: Overall, 1096 cases of cholecystectomies were analysed which revealed female preponderance with peak incidence of non-neoplastic lesion in 4th decade and neoplastic lesions in 5th decade. Gall stones were seen in 52% of cases. Incidence of various lesions was chronic cholecystitis 93.1%, acute cholecystitis 2.91%, chronic follicular cholecystitis 0.72%, xanthogranulomatous cholecystitis 1.1%, cholesterolosis 0.46%, eosinophilic cholecystitis 0.18%, and carcinoma of gall bladder 1.1%.